Discharge Coefficient of a C-Type Piano Key Side Weir at 30° and 120° Sections of a Curved Channel - Mehri, Yaser; Soltani, Jaber; Saneie, Mojtaba; Rostami, Mohhamad (Civil Engineering Journal, 2018)
A piano key side weir (PKSW) is a non-linear weir that discharge exceeds linear weirs by increasing the length in width. PKSW can be used in side weirs with space limitation. As side weirs are extensively used in flood control, water level control in rivers, and water supply channels, it is necessary to use PKSW as side weirs. This research discusses the discharge coefficient of a PKSW by assessing a C-type PKSW at 30° and 120° sections of a channel with a longitudinal curve. Dimensional analysis was used for identifying the parameters effective in the discharge coefficient. The effects of these parameters are examined by analysing the effective parameters. Finally, an empirical relationship has been proposed for determining the discharge coefficient based on the dimensionless parameters for calculating the discharge coefficient with the correlation coefficient of 0.88 and the mean error of 0.091. The influence of the parameter on the PKSW is more than that of the remaining parameters: With an increase in the value of this parameter, considering decreases in the length of the deviation and a lack of submerged inlet keys, the coefficient of discharge increases.